Deconstructing crime and nature or, what does post humanism have to do with criminology? - Francis, Jenny (Critical criminology, 2013)
The aim of this paper is to extend some of the theoretical concerns that Marcus Felson (2006) opens up in Crime and Nature by considering the contribution of post humanist political ecology to the construction of crime and nature that he proposes. Post humanism problematises dichotomous understandings of nature and culture as well as related binaries that follow from that division, suggesting that dominant assumptions about nature and the non human undermine antiracist and feminist efforts. While Felson (2006) takes steps towards troubling the nature/culture binary, he fails to question the constructed character of crime and crime prevention, thereby leaving unarticulated a critical problematisation of the exclusionary logics that underlie dominant practices and ways of thinking as race, sex, class and species fundamentally determine the nature of criminological knowledge. Abstracting crime from social context produces a partial analysis as spaces are reduced to their supposed propensity for criminal activity and some spaces are produced as always already criminal. Without examining and understanding how power relations intersect in the context of crime it is difficult to alter those relations to promote social justice.